(untitled) (Biological Sciences - PJSIR, 2005)
. Interspecific variability and trends in the fecundity of five dominant fish species, namely, Auchanoglanis occidentalis (Bagridae), Brycinus longipinnis (Characidae), Tilipia mariae (Cichlidae), Malapterurus electricus (Malap- teruridae), and Xenomystus nigri (Notopteridae) from Ikpoba river were studied, vis-à-vis certain morphological attri- butes. Estimates of the “b” value (regression coefficient; exponent of length-fecundity relationship) ranged between 0.301 in T. mariae and 3.265 in A. occidentalis with a mean of 1.850. The maximum size of the fish populations examined did not significantly influence the relative magnitude of “b” (regression coefficient). The parameter b of the linear length-fecundity (LF) relationship of the form F= b are also presented. Estimates of b (slope of regression coefficient) ranged from min 2.18 in X. nigri to max 142 in M. electricus. LF data in this study suggested that absolute fecundity of the fish populations was dependent on the cube of their length, and hence body volume. There was a positive allometric functional relationship between the mean total body weight, mean body condition and mean absolute fecundity (p < 0.05). The mean absolute fecundity varied considerably among the families (coefficient of variation, cv = 74.04%). The decreasing order of variance of the mean for absolute fecundity was M. electricus > T. mariae > B. longipinnis > A. occidentalis > X. nigri. The hierarchy of mean absolute fecundity was B. longipinnis > M. electricus > T. mariae > A. occidentalis > X. nigri. There was no significant relationship between the mean absolute fecundity and mean total length (p > 0.05). Interspecific divergence in fecundity and morphometric attributes of these species (cv = 18.8-89.20%) appeared to enhance reproduction isolation or partitioning. This explains, in part, the reason for sustainable coexistence of these fish species within the same habitat in Ikpoba river.